IDEOLOGICAL AND ARTISTIC FEATURES OF “THE ALCHEMIST” - Xoshimova Mohinur (International Journal of Literature and Language Studies, 2026)
Abstract. This article examines the ideological and artistic features of the novel The Alchemist, its genre characteristics, and the author’s literary-aesthetic views.